2012
DOI: 10.1021/nn3024877
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon Inducing Effects for Enhanced Photoelectrochemical Water Splitting: X-ray Absorption Approach to Electronic Structures

Abstract: Artificial photosynthesis using semiconductors has been investigated for more than three decades for the purpose of transferring solar energy into chemical fuels. Numerous studies have revealed that the introduction of plasmonic materials into photochemical reaction can substantially enhance the photo response to the solar splitting of water. Until recently, few systematic studies have provided clear evidence concerning how plasmon excitation and which factor dominates the solar splitting of water in photovolt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
265
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(269 citation statements)
references
References 61 publications
4
265
0
Order By: Relevance
“…These results indicate that water molecules served as the electron donor in the plasmonic photoelectric conversion system and that a nearly stoichiometric evolution of O 2 and H 2 O 2 was achieved as a result of the oxidation of a water molecule with four or two photogenerated holes, respectively. Although numerous studies have achieved water oxidation or water splitting using the irradiation of visible light below wavelengths of 700 nm, 31,[53][54][55][56][57] this study is the first to achieve the stoichiometric evolution of O 2 from water molecules with the irradiation of near-infrared light at a wavelength of 1000 nm (1.24 eV). This result means that water oxidation via a four-electron transfer was accomplished by using a plasmonic photoelectric conversion system.…”
Section: Determining the Electron Source In The Plasmonic Photoelectrmentioning
confidence: 96%
“…These results indicate that water molecules served as the electron donor in the plasmonic photoelectric conversion system and that a nearly stoichiometric evolution of O 2 and H 2 O 2 was achieved as a result of the oxidation of a water molecule with four or two photogenerated holes, respectively. Although numerous studies have achieved water oxidation or water splitting using the irradiation of visible light below wavelengths of 700 nm, 31,[53][54][55][56][57] this study is the first to achieve the stoichiometric evolution of O 2 from water molecules with the irradiation of near-infrared light at a wavelength of 1000 nm (1.24 eV). This result means that water oxidation via a four-electron transfer was accomplished by using a plasmonic photoelectric conversion system.…”
Section: Determining the Electron Source In The Plasmonic Photoelectrmentioning
confidence: 96%
“…Since the first demonstration of solar-assisted water splitting in 1972 [24], wide bandgap semiconductors such as TiO 2 and ZnO have been widely investigated as photoelectrodes [81,82]. Despite their good charge transport properties, they are essentially insensitive to visible and NIR light thus they can convert only a small portion of solar light into chemical energy.…”
Section: Semiconductor Photoelectrodesmentioning
confidence: 99%
“…113 Photovoltage experiment and 3D finite-difference time domain simulation suggested that the enhanced photoactivity was due to the PRET and surface passivation effects in the UV region and hot electron transfer from Au and partially PRET resulting from TiO 2 defect states (Figures 4(b)-4(i)). 114 The photocurrent vs. wavelength data and x-ray absorption spectroscopy result suggested the plasmon-induced hot electrons and additional vacancies created by the plasmon-induced electromagnetic field gave rise to the efficiency enhancements (Figures 4(b)-ii and 4(b)-iii). Enhancement of the PEC efficiency in water splitting via SPR is a complex multifaceted process that requires the careful consideration of various parameters such as morphology, bandgap, band edge position, and midgap state of metal oxides and size, morphology, plasmonic particle areal density, and location of plasmonic metal nanoparticles.…”
Section: -7mentioning
confidence: 93%
“…[112][113][114] The reports attributed the enhancements by the Au attachments mainly to hot electron transfers to semiconductors. Zhang et al demonstrated that Au nanocrystals attached to photonic crystal substrate composed of TiO 2 nanotubes yielded a photocurrent density of ca.…”
Section: -7mentioning
confidence: 99%